Penerapan E-Module Berbasis Problem-Based Learning untuk Meningkatkan Kemampuan Berpikir Kreatif dan Mengurangi Miskonsepsi pada Materi Ekologi Siswa Kelas X MIPA 3 SMA Negeri 6 Surakarta Tahun Pelajaran 2014/2015 - HIDAYATUN, NUNING; KARYANTO, PUGUH; FATMAWATI, UMI (Bioedukasi: Jurnal Pendidikan Biologi, 2015)
This research aimed to improve creative thinking ability and to reduce misconception on ecology in the students of X MIPA 3 of SMA Negeri 6 Surakarta in the academic of 2014/2015 through the application of e-module based on Problem-Based Learning. This research was a Classroom Action Research conducted in two cycles. Each cycle consisted of four stages: planning, acting, observing, and reflecting. The subject of research was the X MIPA 3 graders of SMA Negeri 6 Surakarta in the academic of 2014/2015 consisting of 9 boys and 21 girls. Techniques of collecting data used were essay test to measured creative thinking ability, open ended reasoning of two-tier diagnostic test to measure misconception, observation and interview as the proponent data. The data were analyzed using descriptive qualitative technique consists of three components: data reduction, data presentation, and taking the conclusion. Data validation of this research was triangulation method. Target of the research is an increase 20% on creative thinking aspects and decrease misconception 20% on ecology concepts at the end of the cycle. The result of research showed that there was an increase in each aspect of creative thinking ability: 24.68% of fluency, 34.17% of flexibility, 50% of originality, and 21.67% of elaboration. On the other side, the  result of research also showed that there was a decrease in misconception in the important concepts of ecology including: 43.42% of population, 32.78% of community, 20.6% of food chain and web, and 47.92% of the ecology concept in science, environment, technology and community (salingtemas). The conclusion of this research described that the application of e-module based on Problem-Based Learning is able to improve the ability of creative thinking and reduce the students’ misconception in ecology.